Detection of a Left Superior Vena Cava during a Pacemaker Implantation in Cotonou - SONOU, Arnaud; HOUNKPONOU, MURIELLE KAYIVI ELIANE EPSE AMOUSSOU-GUENOU; CODJO, LEOPOLD; ADJAGBA, MAHOUNA PHILIPPE DOTOU; HOUEHANOU-SONOU, CORINE; DOHOU, HUGUE; ASSANI MOUTAÏROU, Salimatou; TCHABI, YESSOUFOU; HOUENASSI, DÈDONOUGBO MARTIN (My University, 2017)
Persistent left superior vena cava (LSVC)is a rare congenital anomaly. Its prevalence in the general population is 0.1 to 0.5%. LSVC is 5 times rarer when accompanied by an absence of the right superior vena cava (RSVC). We present the case of a 54-year-old man who carries a persistent LSVC without RSVC. Clinically, this patient presented a regular bradycardia at 40 per minute associated with a heart failure syndrome. The electrocardiogram diagnosed a complete atrioventricular block and transthoracic echocardiography showed dilated left heart cavities and a left ventricular ejection fraction of 50%. During the procedure of pacemaker implantation, the probe followed an unusual LSVC-coronary sinus-right atrium path and it was not easy to pass through the tricuspid orifice. We propose a review of the literature on this subject, focusing on the clinical implications of this malformation in cardiac stimulation and in other areas of cardiology.
Keywords: left superior vena cava